Elon Musk - Isaacson, Walter (New York Simon and Schuster, 2023)
When Elon Musk was a kid in South Africa, he was regularly beaten by bullies. One day a group pushed him down some concrete steps and kicked him until his face was a swollen ball of flesh. He was in the hospital for a week. But the physical scars were minor compared to the emotional ones inflicted by his father, an engineer, rogue, and charismatic fantasist.
Includes index
Keywords: Musk, Elon